Transformation of Young Mothers Through the Great Parents School Program: A Study in Sumbersari District, Jember Regency (International Journal of Education and Literature, 2025)
Indonesian families are currently still faced with various challenges, including the low knowledge of mothers about childcare, which can have an impact on child development. This is crucial and a sign that there is a need to improve competence as parents, therefore the Great Parents School provides a way to overcome problems in childcare practices. This study aims to explain the transformation of young mothers who have participated in the Great Parents School program. This study uses a qualitative approach with a descriptive method, the informants in this study are young mothers who have undergone the Great Parents School program and accompanying facilitators, while the data collection process uses observation, interviews, and documentation with the research location in Sumbersari District, Jember Regency. The results of this study show that the empowerment process refers to the ACTORS theory, namely authority, self-confidence, trust, opportunity, responsibility, and support for mothers who have attended the Great Parents School. Mothers who have attended the Great Parents School have experienced improvements in their knowledge, attitudes, and skills related to childcare. This improvement can be seen through their understanding of the role of parents, the application of family functions such as instilling religious values, compassion, and protection, as well as the application of parenting and discipline patterns, and an understanding of communication skills. Therefore, it can be concluded that the Great Parents School serves as a bridge for mothers to become more empowered through improvements in childcare.